An efficient ratiometric fluorescence sensor based on metal-organic frameworks and quantum dots for highly selective detection of 6-mercaptopurine - Jin, Meng; Mou, Zhao-Li; Zhang, Rui-Ling; Liang, Si-Si; Zhang, Zhi-Qi (Biosensors & bioelectronics, 2017)
The development of a simple and accurate quantitative method for the determination of 6-mercaptopurine (6-MP) is of great importance because of its serious side effects. Ratiometric fluorescence (RF) sensors are not subject to interference from environmental factors, and exhibit enhanced precision and accuracy. Therefore, a novel RF sensor for the selective detection of 6-MP was developed based on a dual-emission nanosensor. The nanosensor was fabricated by combining a blue-emission metal-organic framework (MOF) NH2-MIL-53(Al) (λem=425nm) with green-emission 3-mercaptopropionic acid-capped CdTe quantum dots (MPA-CdTe QDs) (λem=528nm) under a single excitation wavelength (335nm). Upon addition of 6-MP, the fluorescence of NH2-MIL-53(Al) in the nanohybrid was selectively quenched due to strong inner filter effects, while the fluorescence of the MPA-CdTe QDs was enhanced. The novel RF sensor exhibited higher selectivity towards 6-MP than CdTe QDs alone, and higher sensitivity than MOFs alone. 6-MP could be detected in the range of 0–50μM with a detection limit of 0.15μM (S/N=3). The developed sensor was applied for the determination of 6-MP in human urine samples and satisfactory results were obtained. Overall, a novel and efficient fluorescence-based method was developed for the detection of 6-MP in biosamples. Schematic illustration of the developed ratiometric fluorescent sensor for 6-MP. [Display omitted] •A ratiometric fluorescence sensor for 6-mercaptopurine (6-MP) was developed.•The sensor was constructed by combining MOF with CdTe quantum dots.•Superior selectivity and comparable sensitivity were achieved.•The sensor was successfully applied to determine 6-MP in urine sample.